Seminal F2-IsoP and RvD1 Levels in Idiopathic Infertile Men - Elena Moretti; Giulia Collodel; Caterina Marcucci; Laura Liguori; Laura Gambera; Cinzia Signorini (Biology)
30 percent of infertile men are diagnosed with idiopathic infertility. This study aimed to assess oxidative stress in the semen of 77 patients with idiopathic infertility by measuring F2-isoprostane (F2-IsoP), resolvin D1 (RvD1) levels, and semen parameters. The presence and localization of 8-IsoProstaglandin F2α were determined using immunofluorescence. No significant correlations were observed for F2-IsoP and RvD1 levels with the semen variables. Based on F2-IsoP levels, individuals were classified into two groups: Group 1 (F2-IsoPs ≤ 29.96 ng/mL, 51%) and Group 2 (F2-IsoPs > 29.96 ng/mL, 49%). In comparison to Group 1, Group 2 showed significantly higher F2-IsoP levels (13.33 ng/mL vs. 44.80 ng/mL; p < 0.05), a lower progressive motility percentage (30% vs. 25%; p < 0.05), and increased RvD1 levels (36.09% vs. 44.94%). Immunofluorescence analysis revealed a different localization of 8-IsoProstaglandin F2α in the ejaculated sperm of Group 1 compared to that observed in Group 2. A weak signal was detected in the sperm tail (Group 1, 79.1% vs. Group 2, 36.9; p < 0.01). In spermatozoa of Group 2 patients, a strong signal in the acrosome, midpiece, and tail was highlighted. These findings suggest the need to test oxidative stress during routine semen analysis in patients with idiopathic infertility to improve diagnosis and treatment.